FREQUENCY AND IMPACT OF ADVERSE DRUG REACTIONS INDUCED BY CARDIOVASCULAR DRUGS AND AFFECTING CARDIOVASCULAR SYSTEM: A NATIONAL 10 YEARs OF SURVEILLANCE. (April 2021) - Polonia, Jorge; Marques, Joana; Lobo, Mariana; Vaz, Ines; Oliveira, Bruno
Abstract: Objective: Cardiovascular (CV) disorders are a leading cause of death. Adverse drug reactions (ADRs) are an important cause of morbidity and mortality. Drugs for treatment of CV disorders and antithrombotic drugs (AT) are commonly prescribed and a cause of serious ADR (SAR). CV system is also a target for non-CV prescribed drugs. In a national survey we identified the most reported ADR associated with CV and AT drugs and the non-CV drugs more prone to affect CV system. Design and method: From January 2006 to December 2015 in a observational retrospective study we analyzed all reports of ADRs (and their determinants) submitted to the National Medicines Regulatory Agency (NMRA). Results: In the study period, 10% (n = 2724) of all ADR reports submitted to the NMRA (N = 28061) were related to CV or Antithrombotic drugs, 73.9% of them were SARs and fatal, 55.6% (n = 1479) in women. Mean age was 62 years and 51% of the episodes occurred in subjects > 65 years. AT drugs were the class most frequently associated with SARS (mainly hemorrhages), 31.1% (n = 956, NOACs 251), followed by modulators of Renin-Angiotensin System (cough and dizziness), 19.97% (n = 544), and by lipid modifying agents (musculoskeletal disorders), 19.6% (n = 534). Reports/year to AT increased 7.7 from 2006 to2013 and 88.5 from 2013 to 2015. CV drugs also produced disorders at gastrointestinal (24, 63%), skin (22, 39%)and nervous system (20, 74%). The most common CV ADR associated with non-CV drugs were hypotension (24.4%) and hypertension (16.5%) most commonly induced by antineoplastic, antibiotics and NSAIDs. Conclusions: Drugs used for treatment of CV disorders & antithrombotic are a common cause of serious ADRs. ADRS involving the CV system by non-CV drugs are also frequent. All can be detected and identified by current pharmacovigilance tools providing valuable information about the safety of post-marked drugs.